Geochronological framework and tectonic setting of the granitic magmatism in the Chaihe–Moguqi region, central Great Xing'an Range, China. (1st December 2015) - Shi, Lu; Zheng, Changqing; Yao, Wengui; Li, Juan; Cui, Fanghua; Gao, Feng; Gao, Yuan; Xu, Jiulei; Han, Xiaomeng
Highlights: Granitic magmatism in the Chaihe–Moguqi region occurred in eight stages: 399 ± 3 Ma, 366–358 Ma, 322–299 Ma, 295–282 Ma, 231–227 Ma, 179–172 Ma, 152–149 Ma and 137–120 Ma. The "Xinghuadukou Group" previously considered to be Precambrian in southern Zhalantun is actually composed of several temporally distinct granites. The collision between Xing'an and Songliao terranes started in the early Late Carboniferous and ended at the beginning of the Permian. Abstract: We compiled and analyzed 56 U–Pb zircon ages, including 38 ages obtained during the present study and 18 from other sources, for granitic rocks of the Chaihe–Moguqi region, central Great Xing'an Range, China. Magmatism in this area can be divided into eight stages: Early Devonian (399 ± 3 Ma), Late Devonian (365–358 Ma), Late Carboniferous (322–299 Ma), Early Permian (295–282 Ma), Late Triassic (231–227 Ma), Early–Middle Jurassic (179–172 Ma), Late Jurassic (152–149 Ma) and Early Cretaceous (137–120 Ma). Granites were mainly emplaced during the latter four (Mesozoic) stages of magmatism. Paleozoic granites formed during several stages, and were associated with oceanic subduction and the amalgamation of crustal blocks in the eastern fragment of the Central Asian Orogenic Belt. The Late Triassic is an important period with respect to the change from the Paleo-Asian Ocean tectonic regime to the circum-Pacific tectonic regime. The formation of Late Triassic granites may have been related to post-orogenic lithospheric extension after closure of the Paleo-Asian Ocean. Early–Middle Jurassic granites resulted from either subduction of the Paleo-Pacific Plate or subduction during the amalgamation of the Jiamusi Massif and the Songliao terrane, whereas the intrusion of Late Jurassic–Early Cretaceous granites was associated with both the subduction of the Paleo-Pacific Plate and the closure of the Mongol–Okhotsk Ocean.